Hubungan Kreativitas Guru PAI dengan Motivasi Siswa Belajar PAI - Ulfa Futri Hasyimiyyah Qissa ‘Ali; Uus Sopandi (STAI Siliwangi Bandung, 2020)
The achievement of a teacher in teaching is determined by several factors, both internal and external factors. Internal factors consist of motivation, self-confidence, and creativity of the teacher himself. While external factors are more emphasized on the facilities and climate of the school. Every progress achieved by humans always involves creativity. When humans long for productivity, effectiveness, efficiency, and even happiness that is better and higher than what was previously achieved, then creativity is the basis for achieving it. Creativity is basically a gift which is given by God to every human being, which is in the form of the ability to create (creative) and innovate. The implementation of one's creativity is not the same, depending on the extent to which the person is willing and able to turn his creativity into a creation or work.